Marital Satisfaction of Pastors in Long-distance Marriage: The Role of Self-compassion and Spousal Social Support - Febryani, Irma; Adiyanti, Maria Goretti; Soetjiningsih, Christiana Hari (Kuras Institute, 2025)
Marital satisfaction is a condition desired by every married couple. This becomes more challenging when faced with the reality of a long-distance marriage. The study aimed to examine the role of self-compassion and spousal social support in predicting marital satisfaction. Participants in this study were 100 GPIB pastors in 19 provinces who have been in long-distance marriage for 1-25 years. Data collection used The Self-Compassion Scale (SCS), The Receipt of Spousal Support Scale (RSSS) and ENRICH Marital Satisfaction Scale (EMSS), which were distributed by sending questionnaires via Google form. Data analysis was conducted quantitatively using multiple linear regression techniques. The findings indicate that self-compassion and spousal social support simultaneously predict marital satisfaction. Partially, spousal social support has a greater predictive power on pastors’ marital satisfaction than self-compassion. The implications of this study for pastor couples in long distance marriage are expected to emphasize the important of partners in providing social support to achieve marital satisfaction.